2019
DOI: 10.2147/cmar.s191432
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic values of preoperative platelet-to-lymphocyte ratio, albumin and hemoglobin in patients with non-metastatic colon cancer</p>

Abstract: Purpose: Preoperative platelet-to-monocyte ratio (PLR), albumin and hemoglobin are suggested prognostic indicators in various malignancies. However, the prognostic values of PLR, albumin and hemoglobin remain elusive. The objective of the present study was to evaluate the prognostic values of PLR, albumin and hemoglobin in stage I-III colon cancer. Patients and methods: A total of 312 patients with non-metastatic colon cancer undergoing curative resection were enrolled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Malnutrition can lead to the decline of immune function in cancer patients, thus increasing the risk of postoperative complications and tumor progression. 21 Previous studies have reported that hypoalbuminemia is associated with disease progression and poor prognosis in patients with colon cancer, 22 pancreatic cancer, 23 non-small cell lung cancer, 24 ovarian cancer, 25 and GC. 26 Furthermore, this study shows that preoperative CEA is an independent prognostic factor of survival, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition can lead to the decline of immune function in cancer patients, thus increasing the risk of postoperative complications and tumor progression. 21 Previous studies have reported that hypoalbuminemia is associated with disease progression and poor prognosis in patients with colon cancer, 22 pancreatic cancer, 23 non-small cell lung cancer, 24 ovarian cancer, 25 and GC. 26 Furthermore, this study shows that preoperative CEA is an independent prognostic factor of survival, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was reported that platelets may exhibit an important effect on inflammatory modulation [ 29 , 30 ] by promoting the release of inflammatory cytokines that initiate the inflammatory process. [ 31 , 32 ] In addition, evidence has also indicated that lymphocytes are also an important inflammatory factor in different diseases, such as cardiovascular diseases [ 33 ] and type 2 diabetes. [34] Therefore, the PLR was proposed as a new marker for inflammation in various disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large tumor size was found to be associated with poor OS in those receiving chemotherapy [26]. Additionally, other studies have indicated that younger age [27] and low HGB are associated with poor prognosis in patients [28]. We speculate that these parameters contribute to the link between poor DFS and high postoperative FBG in CRC.…”
Section: Discussionmentioning
confidence: 60%